Особенности реализации принципа интеграции в образовательном процессе назарбаев интеллектуальной школы - Сапаков, Д.Н.; Татимбеков, Р. Ш. (My University, 2016)
This article considers the problems of integrative approach usage in the educational process of Nazarbayev Intellectual school. It characterizes various types of content integration according to the distinguishing features of educational program and educational process organization.
Keywords: integration; intradisciplinary; interdisciplinary; transdisciplinary